2019
DOI: 10.3390/su11072119
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Value Creation, Survival, and Growth of the Company: A Critical Perspective in the Sustainability Balanced Scorecard (SBSC)

Abstract: The issue of sustainability in company strategy has assumed crucial relevance in recent years. Many companies have implemented specific environmental and sustainability management systems such as the Sustainability Balanced Scorecard (SBSC), which integrates sustainability and the traditional Balanced Scorecard (BSC). However, environmental and sustainability aspects are often not linked to economic success, and qualitative analysis is not considered adequately by managers. Therefore, these dimensions remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 64 publications
1
73
0
1
Order By: Relevance
“…The extended form of the balanced scorecard, widely known as a sustainable balanced scorecard, integrates BSC's four perspectives into sustainability [70]. Moreover, the natural evaluation of strategic thinking that meets the expectations of the environment and society is a known sustainable strategic management system provided that its political and regulatory factors are stable to support the business environment [71,72].…”
Section: Balanced Scorecard and Sustainable Developmentmentioning
confidence: 99%
“…The extended form of the balanced scorecard, widely known as a sustainable balanced scorecard, integrates BSC's four perspectives into sustainability [70]. Moreover, the natural evaluation of strategic thinking that meets the expectations of the environment and society is a known sustainable strategic management system provided that its political and regulatory factors are stable to support the business environment [71,72].…”
Section: Balanced Scorecard and Sustainable Developmentmentioning
confidence: 99%
“…There is also a problem with this procedure which has revealed that it is difficult to choose, correct and then communicate the aims that need to be accomplished. In fact, the absence of a connection between managers and objectives was identified when developing the Balanced Scorecard concept [37,38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Via field investigations, it can be found that one of the most important reasons for the competitive inferiority of wood biomass power generation companies in China is the unstable supply of biomass materials. Moreover, from the point of view of the enterprise itself, environmental and sustainability aspects are often not linked to economic success [23]. Based on these factors, optimizing the cost of the raw material supply chain is a top priority for forest biomass power generation enterprises.…”
Section: Objective Functionsmentioning
confidence: 99%